Coping strategies following the diagnosis of a fetal anomaly: A scoping review - Zhang, Tingting; Chen, Wei-Ti; He, Qingnan; Li, Ying; Peng, Huiting; Xie, Jiaying; Hu, Hengfen; Qin, Chunxiang (Frontiers in Public Health, 2023)
Introduction: Many women experience severe emotional distress (such as grief, depression, and anxiety) following a diagnosis of fetal anomaly. The ability to cope with stressful events and regulate emotions across diverse situations may play a primary role in psychological wellbeing. This study aim to presenting coping strategies after disclosing of fetal anomaly to the pregnant women. Methods: This is a scoping review based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) extension for scoping reviews (PRISMA-ScR). Electronic databases including Web of Science (WOS, BCI, KJD, MEDLINE, RSCI, SCIELO), CINAHL and EBSCO PsycARTICLES were used to search for primary studies from inception of each database to 2021. The keywords were determined by existing literature and included: “fetal anomaly”, “fetal abnormality”, “foetal anomaly”, “foetal abnormality” AND “cope”, “coping”, “deal”, “manage”, “adapt*”, “emotion* regulate*”, with the use of Boolean operators AND/OR. A total of 16 articles were reviewed followed by advancing scoping review methodology of Arksey and O’Malley’s framework. Results: We identified 52 coping strategies used 5 questionnaires in 7 quantitative studies and one mixed-methods study in this review. The relationship between coping strategies and mental distress was explored. However, the results were inconsistent and incomparable. We synthesized four coping categories from qualitative studies and presented them in an intersection. Conclusion: This scoping review identified the coping strategies of women with a diagnosis of fetal anomaly during pregnancy. The relationship between coping strategies and mental distress was uncertainty and need more explorations. We considered an appropriate measurement should be necessary for the research of coping in women diagnosed with fetal anomaly pregnancy.